2016
DOI: 10.1007/s12550-016-0245-y
|View full text |Cite
|
Sign up to set email alerts
|

The potential effects of antioxidant feed additives in mitigating the adverse effects of corn naturally contaminated with Fusarium mycotoxins on antioxidant systems in the intestinal mucosa, plasma, and liver in weaned pigs

Abstract: Seventy-two piglets (6.0 kg BW) were randomly distributed within six different dietary treatments to evaluate the effect of deoxynivalenol (DON) and the potential of four antioxidant feed additives in mitigating the adverse effects of DON on growth performances and oxidative status. Dietary treatments were as follows: control diet 0.8 mg/kg DON; contaminated diet (DON-contaminated diet) 3.1 mg/kg DON; and four contaminated diets, each supplemented with a different antioxidant feed additive, DON + vitamins, DON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 70 publications
4
17
0
Order By: Relevance
“…In the present study, supplementation with 0.3-1.2 g/kg of MMT did not appear to influence T-SOD activity in the jejunal or ileal mucosa, but jejunal T-AOC of the group fed 0.3 g MMT/kg increased significantly. These findings were similar to those ofThanh et al (2016), who reported that adding aluminosilicate adsorbent to DON-contaminated diets had shown no significant increases in the activity of SOD and T-AOC in the intestine of piglets, but improved GSH-Px activity of the ileal mucosa. As one of the most important terminal products of lipid peroxidation, MDA is commonly used for monitoring lipid oxidation…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, supplementation with 0.3-1.2 g/kg of MMT did not appear to influence T-SOD activity in the jejunal or ileal mucosa, but jejunal T-AOC of the group fed 0.3 g MMT/kg increased significantly. These findings were similar to those ofThanh et al (2016), who reported that adding aluminosilicate adsorbent to DON-contaminated diets had shown no significant increases in the activity of SOD and T-AOC in the intestine of piglets, but improved GSH-Px activity of the ileal mucosa. As one of the most important terminal products of lipid peroxidation, MDA is commonly used for monitoring lipid oxidation…”
supporting
confidence: 91%
“…centration in the ileum. This result was similar to the finding ofThanh et al (2016). When the intestinal endotoxin is absorbed by MMT, its bioavailability reduces greatly.…”
supporting
confidence: 89%
“…An expanding amount of literature has shown that co-contamination of multiple mycotoxins in cereals is more likely to occur than a single mycotoxicosis, especially as DON and ZEA can both originate from the Fusarium species under similar conditions [ 44 , 45 ]. Moreover, a higher toxicological risk due to synergistic and additive interactions between multiple mycotoxins has become highly noticeable, especially in mice and pigs [ 46 , 47 ]. On the contrary, toxicological synergism between DON and ZEA were rarely observed in poultry studies, as it seemed that even high dietary concentrations were not enough to cause detrimental effects on performance or reproduction [ 32 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Van Le Thanh et al . () showed that quercetin could reduce liver malondialdehyde content in pigs (Van Le Thanh et al ., ). Naringenin is a https://en.wikipedia.org/wiki/Flavanone, which is a type of flavonoid, which is considered to have a bioactive effect on human health as an https://en.wikipedia.org/wiki/Antioxidant, https://en.wikipedia.org/wiki/Free_radical https://en.wikipedia.org/wiki/Radical_scavenger, an anti‐inflammatory agent, https://en.wikipedia.org/wiki/Carbohydrate https://en.wikipedia.org/wiki/Metabolism promoter, and https://en.wikipedia.org/wiki/Immune_system modulator.…”
Section: Prospective Phytochemicals May Be Used In Research For Reducmentioning
confidence: 99%